PENGEMBANGAN DESA WISATA JATISARI EDUPARK MELALUI PENINGKATAN KUALITAS SARANA PRASARANA DAN KELEMBAGAAN - Sulistyono, If Bambang; Irianto, Heru; Riptanti, Erlyna Wida; Herawati, Aktavia (Universitas Padjadjaran, 2026)
Jatisari Edupark is an innovative tourism village situated in Jatisari Village, Jatisrono District, Wonogiri Regency. Jatisari Edupark embodies the principles of ecotourism, agricultural education, outdoor activities, and gastronomic experiences. The objective of this initiative is to transform Jatisari Village into a tourism destination—Jatisari Edupark—by enhancing the level of services, infrastructure, and institutions. Since its debut in 2022, this tourism village has faced numerous challenges, including inadequate facilities and infrastructure for visitors. The identified root problems comprise the absence of shade due to a lack of shade-providing vegetation, limited and homogeneous outbound equipment facilities, unattractive photo opportunities, inadequate promotion of the tourist village, and the nonexistence of a Tourism Awareness Group (TAG) institution. The suggested remedies encompass the planting of shade trees, the introduction of outbound equipment, landscaping with flowering plants, the creation of promotional content for social media dissemination, and the enhancement of the institutional structure. The employed strategy involves active participation and engagement from the Jatisari Edupark managers, along with direct involvement in all activities, monitoring, and assessment of outcomes. The outcomes of the activities indicated that shade plants—namely pule and ketapang kencana trees—were planted, with ten specimens of each type. Landscaping involved the planting of diverse ornamental flora, including golden shower, tapak dara, chrysanthemum, sunflower, asoka, and bougainvillea. Outbound equipment has been supplied, comprising safety helmets and rafts for rafting and outbound activities. Furthermore, training on the development of promotional content for social media has been conducted. Consequently, the site has become increasingly shaded, the amenities for outdoor activities are now sufficient, and members of the Tourism Awareness Group have successfully uploaded promotional content on social media. Jatisari Edupark merupakan rintisan desa wisata yang berada di Desa Jatisari, Kecamatan Jatisrono, Kabupaten Wonogiri. Jatisari Edupark mengusung konsep wisata alam, edukasi di bidang pertanian, outbound dan kuliner. Tujuan dari kegiatan ini adalah pengembangan Desa Jatisari menjadi Desa Wisata Jatisari Edupark melalui peningkatan kualitas sarana dan prasarana serta kelembagaan. Berbagai permasalahan dihadapi dalam mengembangkan rintisan desa wisata ini sejak diresmikannya pada tahun 2022, diantaranya minimnya fasilitas sarana prasarana untuk wisatawan. Akar permasalahan yang ditemukan diantaranya kurang teduhnya lokasi karena belum ada tumbuhan peneduh, fasilitas peralatan outbound masih terbatas dan belum variatif, spot foto pemandangan yang kurang menarik, promosi desa wisata belum masif, dan belum adanya kelembagaan kelompok sadar wisata (Pokdarwis). Solusi yang ditawarkan meliputi penanaman tanaman peneduh, introduksi peralatan outbound, penataan lansekap dengan tanaman bunga, membuat konten promosi dan melakukan promosi di media sosial, dan penguatan kelembagaan Pokdarwis. Metode yang diterapkan adalah partisipatif aktif dari pengelola Jatisari Edupark dan pelibatan langsung di seluruh kegiatan, monitoring dan evaluasi hasil kegiatan. Hasil kegiatan diperoleh bahwa telah dilakukan penanaman tanaman peneduh yaitu tanaman pule dan ketapang kencana masing-masing sebanyak 10 pohon. Dilakukan penataan lansekap dengan menanam berbagai tanaman hias meliputi bunga jatuh emas, bunga tapak doro, bunga krisan, bunga matahari, bunga asoka dan bunga kertas. Telah dilakukan pemberian peralatan outbond berupa helm pengaman dan ban untuk rafting/outbond. Selain itu juga telah dilakukan pelatihan pembuatan konten promosi untuk diunggah di media sosial. Hasilnya, lokasi menjadi lebih teduh, sarana prasarana untuk outbond memadai, dan anggota kelompok sadar wisata mampu mengunggah konten di media sosial untuk promosi.